EFFECT OF REVOLVING FUNDS, COMPETENCE OF HUMAN RESOURCES, WORKING CAPITAL, CREDIT RISK ON THE PERFORMANCE OF MICROFINANCE INSTITUTIONS (AGRIBUSINESS (MFI-A) MODERATED BY RISK MANAGEMENT TRAINING - Hasanudin, Hasanudin; Nurwulandari, Andini; Nurhayati, Yanti (2021)
This study aims to determine the effect of revolving funds, human resource competence, working capital, and credit risk on the performance of Agribusiness Microfinance Institutions moderated by risk management training. This study uses mixed-method research with two types of data, namely quantitative and qualitative data. Sources of data in this study consisted of primary sources and secondary sources. Data collection techniques in this study used interview, observation and questionnaire techniques. The research sample was taken by random sampling, where samples of MFI-A were in three regions, namely Central Java, West Java and Banten, totalling 145 MFI-A. The data analysis method in this study uses the Validity Test, Reliability Test, and Hypothesis Testing. Based on the results of the analysis and discussion, it can be concluded that: 1) There is a positive and significant effect of the revolving fund variable on the performance of MFI-A; 2) There is a positive and significant influence of the H.R. competency variable on the performance of MFI-A; 3) There is a positive and significant effect of the working capital variable on the performance of MFI-A, 4) There is a positive and significant influence of credit risk on the performance of MFI-A, and 5) risk management training can be moderated by strengthening the influence of H.R. competence on the performance of MFI-A.